The changes of blood coagulation and fibrinolysis during extra corpora circulation - FUKUYAMA M.; WEI C. M.; IMURA M.; HATTORI R.; SAITO K.; YADA I.; YUASA H.; KUSAGAWA M. (Jinko Zoki, 1986)
The changes of blood coagulation and fibrinolysis during extra corporal circulation (ECC) were studied in 20 cases. Fibrinopeptid A, a sensitive and specific factor of blood coagulation activity, did not increased during ECC, but elevated after heparin neutralization with protamine. FDP increased remarkably during ECC. Antithrombin III, α2 plasmin inhibiter, plasminogen and fibrinogen decreased during ECC. These data suggested that blood coagulation was well controled by heparin, but fibrinogenolysis was activated during ECC 開心術症例20例を対象とし, 体外循環前後の凝固・線溶系の変化について検討した。検査項目は, フィブリノペプタイドA(FPA), フィブリノーゲン(Fbg), アンチトロンビンIII(ATIII), α2プラスミンインヒビタ(α2PI), プラスミノーゲン(Plg), FDPで, 体外循環前, 体外循環5分, 60分, 120分, ヘパリン中和直後, 中和後3時間, 6時間の計7回採血を行った。FPAは体外循環前値が6.1±4.0ng/mlで, 体外循環中は増加せず, ヘパリン中和直後に14.8±11.5ng/mlと有意に増加した。FDPは体外循環前値が6.2±6.0μg/mlで, 体外循環120分には274.6±111.1μg/mlと増如した。一方Fbg, α2PI, ATIII, Plg, は体外循環中減少した。以上の結果より体外循環中凝固活性はヘパリンにより十分に抑制されているものの, 線溶活性, 特に一次線溶が亢進している可能性が示唆された。